Measurement of inferior colliculus volume based on MRI image stacks and its relationship with age and hearing status - Pingling Kwok; Otto Gleich; Peter Koch; Gudrun Schenkl; Nina Koch; Christopher Bohr (PLoS ONE, 2025)
The inferior colliculus is a key nucleus in the central auditory pathway, integrating acoustic stimuli from both cochleae and playing a crucial role in sound localization. It undergoes functional and structural development in childhood and experiences age-related degeneration later in life, contributing to the progression of age-related hearing loss. This study aims at finding out, whether the volume of the human inferior colliculus can be determined by analysis of routinely performed MRIs and whether there is any age-related variation. A further goal is to detect correlations between volume and existing hearing loss of the patients. A retrospective search in the data of the Regensburg ENT department was done. 123 MRI datasets were used to mark the voxels of the inferior colliculus on the MRI layers. The volumes could then be calculated by using the respective DICOM data and were correlated with age, gender and hearing status of the patients. Results suggested that a voxel-based method on routine clinical MRI stacks to determine the volume of the inferior colliculus is possible. The volume shows an age-dependency. There is a growth from infancy until adulthood and a significant decrease in patients over the age of 60 years. Left and right inferior colliculi do not show any systematic asymmetry in volume. There is no difference between females and males. In the group with asymmetric hearing (n = 13) a significant reduction of the volume on the deprived side (p = 0.036) was found. The proportion of subjects with severe hearing loss at least on one side was significantly higher in the old (>60 years) as compared to younger adults (10 to 60 years), suggesting that severe hearing loss may be associated with a reduced volume of the inferior colliculus in aged humans.